2019
DOI: 10.1002/oby.22424
|View full text |Cite
|
Sign up to set email alerts
|

Leisure‐Time Sedentary Behavior and Obesity Among 116,762 Adolescents Aged 12‐15 Years from 41 Low‐ and Middle‐Income Countries

Abstract: Objective Rates of adolescent obesity are increasing worldwide, with steeper increases being observed in low‐ and middle‐income countries (LMICs). Sedentary behavior (SB) has been associated with various physical and mental health conditions. Little is known about the association between SB and obesity among adolescents in LMICs. This cross‐sectional study explored the associations between SB and obesity in adolescents from 41 LMICs. Methods Obesity was measured using BMI; SB was assessed through self‐report a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 31 publications
2
25
0
Order By: Relevance
“…This excluded time at school and when doing homework. In accordance with previous research showing that engaging in sedentary behavior for ≥3 h/day is associated with significant health risks [ 5 , 24 28 ], the variable was dichotomized as ≥3 h/day (high LTSB) or not.…”
Section: Methodsmentioning
confidence: 99%
“…This excluded time at school and when doing homework. In accordance with previous research showing that engaging in sedentary behavior for ≥3 h/day is associated with significant health risks [ 5 , 24 28 ], the variable was dichotomized as ≥3 h/day (high LTSB) or not.…”
Section: Methodsmentioning
confidence: 99%
“…with response options being 'never', 'rarely', 'sometimes', 'most of the time', and 'always'. This food insecurity variable was used as a proxy of socioeconomic status [23,24] as the GSHS did not include any direct measure of socioeconomic status. Trained survey staff measured participants' height and weight [23].…”
Section: Covariatesmentioning
confidence: 99%
“…This food insecurity variable was used as a proxy of socioeconomic status [23,24] as the GSHS did not include any direct measure of socioeconomic status. Trained survey staff measured participants' height and weight [23]. Body mass index (BMI) was categorised as underweight (BMI <−2 Standard Deviation [SD]), overweight (BMI > +1SD), and obese (BMI > +2SD), relative to median BMI, by age and gender based on the WHO Child Growth Standards [21].…”
Section: Covariatesmentioning
confidence: 99%
“…Multinational studies allow exploration of sedentary behavior correlates irrespective of national policies and available facilities, and at the same time allow comparison between countries in order to investigate the role of these policies and available facilities in different countries. Previous multinational studies in adolescents from LMICs have shown that sedentary behavior is associated with obesity [16], depression [17], loneliness [18], and fast food and carbonated soft drink consumption [19]. However, there is limited information on other important correlates from a global perspective.…”
Section: Introductionmentioning
confidence: 99%